Trigger mortis ebook With original material by ian fleming. - Horowitz, Anthony (James Bond, 2015)
"Horowitz delivers an entertainment sure to please James Bond fans." — Publishers Weekly (starred review) "The heart of any good thriller is the plot, and...Horowitz doesn't disappoint." — New York Times Book Review Blockbuster author Anthony Horowitz delivers a riveting and stylish take on literary legend James Bond (authorized by the Ian Fleming Estate) with a story that unfolds in the 1950s—and is the first new Bond novel to feature recently discovered original material by Ian Fleming. It's 1957 and James Bond (agent 007) has only just survived his showdown with Auric Goldfinger at Fort Knox. By his side is Pussy Galore, who was with him at the end. Unknown to either of them, the USSR and the West are in a deadly struggle for technological superiority. And SMERSH is back. The Soviet counter-intelligence agency plans to sabotage a Grand Prix race at the most dangerous track in Europe. But it's Bond who finds himself in the driving seat and events take an unexpected turn when he observes a suspicious meeting between SMERSH's driver and a sinister Korean millionaire, Jai Seong Sin. Soon Bond is pitched into an entirely different race uncovering a plan that could bring the West to its knees. Welcoming back familiar faces, including M and Miss Moneypenny, international bestselling author Anthony Horowitz ticks all the boxes: speed, danger, strong women and fiendish villains, to reinvent the golden age of Bond in this brilliantly gripping adventure. Trigger Mortis is also the first James Bond novel to feature previously unseen Ian Fleming material. This is James Bond as Fleming imagined him.